Pelaksanaan Program Voluntary Conseling and Testing Di Wilayah Kerja Puskesmas II Denpasar Selatan - Ariesta Krisna, I Gst. Made Bagus; Zuryani, Nazrina; Kebayantini, Ni Luh Nyoman (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
Human Immunodefisiency Virus (HIV) is a virus that affect immunity system and it weaken body ability to counter infection and desease. Concerning to high number of HIV/AIDS cases in Denpasar, the government create the VCT (Voluntary Conseling and Testing) programs to prevent and overcome the desease at Jempiring Asri clinic on Puskesmas II Denpasar Selatan. the purpose of this study are to identify the process and implementation mechanism of Voluntary Conseling and Testing (VCT) programs implemented by Jempiring Asri clinic and discover the implications of VCT program implementation on public health behavior to overcome HIV / AIDS. The data in this research was collect using observation method, interview, document study and library research, and the the concept of health behavior by Green (1990) was analyzed to describe various efforts conducted by comunity healthcare through VCT Jempiring Asri clinic to detect and treat HIV/AIDS case as early as possible. The result of this study shows that VCT program processes and mechanisms are implemented in three stages. first: pre-counseling to motivate and guide patients to openly and honestly admit their health behaviors. second: conduct laboratory testing, to determine whether the patient is positive or non HIV-infected. the last stage: Post-counseling conducted to take intensive care to guide patients for treatment and therapy. The implications of the program's implementation relate to the changes in health behaviors, avoidance and prevention of HIV / AIDS transmission, as well as continuously and discipline of antiretroviral treatment (ARV). Keyword : HIV/AIDS, VCT, Behavior changes